An Investigation of Hate Speech in Italian (Helsinki University Press, 2024)
Language is a key element in constructing and reinforcing social identities. Through hate speech, language becomes an instrument of creating and spreading stereotypes, discrimination, and social injustices based on attributes such as race, ethnicity, religion, gender, nationality, political ideology, disability, or sexual orientation. The rise of digital communication, especially social media, has made hate speech a major topic of research in various fields. An Investigation of Hate Speech in Italian analyses hate speech from a linguistic perspective. The focus is not only on lexical means, but also on more subtle grammatical and pragmatic strategies related to implicit meanings or conversational dynamics. The volume identifies the common linguistic characteristics of hate speech in different domains of communication and explores criteria that can help distinguish between hate speech and freedom of expression. The studies in this volume focus on Italian, but the methods and findings can easily be extended to other languages for comparative and contrastive purposes. The chapters utilize extensive research data. Social media platforms have provided linguistic data that would otherwise be challenging to collect and analyse systematically. The chapters allow readers to link linguistic insights to different real-world contexts, helping them understand the impact language has on various aspects of life and society.